Bridging theory and grassroots insight: Assessing the capacity of local communities in evaluating cultural heritage significance - Muti’ah Rihul Jannah (Journal of Socio-Cultural Sustainability and Resilience, 2026)
Background: The city of Yogyakarta as a special area that has a high historical value and a wealth of historical heritage is deemed necessary to pay more attention to these things. Moreover, the rapid development and massive development that is currently happening can threaten the sustainability of the existing cultural heritage areas. One of the Cultural Conservation Areas that may be threatened is the Kotagede area as a witness to the history of the glory of the Islamic Mataram Kingdom and the forerunner of the formation of the city of Yogyakarta. This area is currently and will continue to undergo several changes. The local community as one of the stakeholders has a very important role in harmonizing the changes that occur. Research to see the extent to which the assessment of the significance of cultural heritage both theoretically and through local community criteria becomes very significant to be carried out. Methods: This study uses a deductive-mix method approach and statistical analysis uses a Likert-scaled technique. The unit of observation of this study includes 6 objects of cultural heritage found in the Kotagede Cultural Heritage Area, namely Kotagede Market, Mataram Gedhe Mosque, Tomb Complex of the Founders of the Kingdom & Sendang Seliran, Kampung Alun-Alun (“Between Two Gates”), Kedhaton, and Ruins. Cepuri Fort. The analysis was carried out in three stages. The first stage is to assess the significance of cultural heritage based on literacy studies and secondary data. The second stage is to assess the significance of cultural heritage by involving the role of local communities through the development of criteria. The next stage is to analyze the significance of each proposed criterion based on public perception. Findings: Summarize the main findings, including specific effect sizes and their statistical significance, if possible. The result of this research is that all research objects have important significance values, where there is only a slight difference between the assessment based on literature study and based on public perception. Conclusion: In conclusion, this study highlights that all cultural heritage sites in the Kotagede area hold significant value, with only minor differences between theoretical assessments and local community perceptions. It also emphasizes that local communities possess comparable capacity and insight to other stakeholders in evaluating the significance of cultural heritage. Novelty/Originality of this article: Another finding from this study is that local communities also have the same capacity and capability as other stakeholders to assess the significance of cultural heritage.